1959
DOI: 10.1083/jcb.5.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Electron Microscopy of the Tapetum Lucidum of the Cat

Abstract: The fine structure of the tapetum of the cat eye has been investigated by electron microscopy. The tapetum is made up of modified choroidal cells, seen as polygonal plates grouped around penetrating blood vessels which terminate in the anastomosing capillary network of the choriocapillaris. The tapetal cells are rectangular in cross-section, set in regular brick-like rows, and attain a depth of some thirty-five cell layers in the central region. This number is gradually reduced peripherally, and is replaced at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

1959
1959
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 6 publications
2
48
0
Order By: Relevance
“…E. de Robertis (personal communication) states that 'the external limiting membrane is made of fine interlacing expansions of the Muller cells' and does not consider that it would impede the advance of a micropipette electrode. On the other hand, Bernstein & Pease (1959) show no clear discontinuities of Bruch's membrane in electron micrographs from cat retinas, and L. K. Garron and M. L. Feeney (personal communication) report similar results from human material. Thus it seems reasonable that Bruch's membrane, but not the external limiting membrane, could have a high electrical resistance.…”
Section: -8 Sec U_idsupporting
confidence: 64%
“…E. de Robertis (personal communication) states that 'the external limiting membrane is made of fine interlacing expansions of the Muller cells' and does not consider that it would impede the advance of a micropipette electrode. On the other hand, Bernstein & Pease (1959) show no clear discontinuities of Bruch's membrane in electron micrographs from cat retinas, and L. K. Garron and M. L. Feeney (personal communication) report similar results from human material. Thus it seems reasonable that Bruch's membrane, but not the external limiting membrane, could have a high electrical resistance.…”
Section: -8 Sec U_idsupporting
confidence: 64%
“…Bruch's membrane is usually defined as the membrane lying between the choriocapillaris and the pigment epithelium. This definition will be maintained here, contrary to the terminology of Bernstein & Pease (1959). By this conventional definition Bruch's membrane in the cat consists only of the basement membrane of the pigment epithelium, which is only about 0x25 , or less in thickness (Bernstein & Pease, 1959).…”
Section: Resultsmentioning
confidence: 65%
“…This definition will be maintained here, contrary to the terminology of Bernstein & Pease (1959). By this conventional definition Bruch's membrane in the cat consists only of the basement membrane of the pigment epithelium, which is only about 0x25 , or less in thickness (Bernstein & Pease, 1959). Thus it cannot be resolved by the light microscope, but is clearly identified by the spindle-shaped nuclei on its choroidal surface.…”
Section: Resultsmentioning
confidence: 68%
“…l b. In published electron micrographs (Bernstein & Pease, 1959;Pedler, 1963) one set lies within about 15°o f the plane of the choroidal surface; the others are inclined to these at angles which vary from bundle to bundle so that although the lattices in some bundles can be described as square and in others as hexagonal, intermediate cases occur. The extent to which this represents a modification of the in vivo structure will be discussed.…”
Section: Introductionmentioning
confidence: 99%
“…However, Gunter, Harding & Stiles (1951) and Weale (1953), having measured the spectral reflectivity, concluded that pigments were primarily responsible for the appearance. Since then, electron microscope studies have been made by Bernstein & Pease (1959) and Pedler (1963) which show that within each bundle the rodlets are arrayed with great regularity and the spacing between centres of adjacent rodlets is comparable to a wave-length of visible light. Because of this, Pedler suggests that reflexion according to Bragg's Law may occur from the layers of rodlets, rather as X-rays are diffracted by atoms in a crystal.…”
Section: Introductionmentioning
confidence: 99%